Photocatalytic removal of benzene over Ti3C2Tx MXene and TiO2–MXene composite materials under solar and NIR irradiation. Issue 2 (14th December 2021) - Sergiienko, Sergii A.; Tobaldi, David M.; Lajaunie, Luc; Lopes, Daniela V.; Constantinescu, Gabriel; Shaula, Aliaksandr L.; Shcherban, Nataliya D.; Shkepu, Viacheslav I.; Calvino, José J.; Frade, Jorge R.; Labrincha, João A.; Kovalevsky, Andrei V.
Abstract : The TiO2 /MXene composites prepared by different routes were assessed towards the degradation of organic pollutants under simulated solar light. A notable photocatalytic activity of bare MXene under near infra-red light was discovered. Abstract : MXenes, a family of two-dimensional (2D) transition metal carbides, nitrides and carbonitrides based on earth-abundant constituents, are prospective candidates for energy conversion applications, including photocatalysis. While the activity of individual MXenes towards various photocatalytic processes is still debatable, these materials were proved to be excellent co-catalysts, accelerating the charge separation and suppressing the exciton recombination. Titanium-containing MXenes are well compatible with the classical TiO2 photocatalyst. The TiO2 component can be directly grown on MXene sheets by in situ oxidation, representing a mainstream processing approach for such composites. In this study, an essentially different approach has been implemented: a series of TiO2 –MXene composite materials with controlled composition and both reference end members were prepared, involving two different strategies for mixing sol–gel-derived TiO2 nanopowder with the Ti3 C2 T x component, which was obtained by HF etching of self-propagating high-temperature synthesis products containing modified MAX phase Ti3 C2 Al z ( z > 1) with nominal aluminium excess. The prospects of such composites for the degradation of organic pollutants under simulated solar light, using benzene as a model system, were demonstrated and analysed in combination with their structural, microstructural and optical properties. A notable photocatalytic activity of bare MXene under near infrared light was discovered, suggesting further prospects for light-to-energy harvesting spanning from UV-A to NIR and applications in biomedical imaging and sensors.